Proceedings of the 1st International Conference on Advanced Research Methods and Analytics 2016
DOI: 10.4995/carma2016.2016.3106
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Orientation and Firm Performance in the Context of Upper Echelon Theory

Abstract: Citation for published item:qliD xF nd rughesD wF nd wlletD yF nd urmD eF @PHITA 9intrepreneuril orienttion nd (rm performne in the ontext of upper ehelon theoryF9D in gewe PHIT X Ist snterntionl gonferene on edvned eserh wethods nd enlytisD tuly T E UD PHITD leniD pinF leniX niversitt olit eni de l eniD pF IRTF Further information on publisher's website: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…, 2009). Using upper echelons theory, Gali et al. (2016) found that the CEO's greed and overconfidence moderate the curvilinear relationship between EO and the firm's performance.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…, 2009). Using upper echelons theory, Gali et al. (2016) found that the CEO's greed and overconfidence moderate the curvilinear relationship between EO and the firm's performance.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…the upper echelons, matter. A few studies have focused on the role of CEO power in moderating EO and firm's performance relationship; for example, the CEO's greed and overconfidence (Gali et al. , 2016), transforming leadership of the CEO (Engelen et al.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Primarily, the research concerning narcissism revealed the negative effect of the conduct for organization whereas a few works also commented that many narcissistic CEOs pull out enormously prosperous management (Colbert et al , 2014). The originator CEOs of the organization experience individuality regarding personal and production wellbeing thus the central undertaking is the growth of the CEOs personal goals, in the course of heavy affecting affiliations between the originator CEO and their firms (Gali et al , 2016). It is suggested in the present literature that future scholars should find out narcissism as a moderator in the association between founder CEO and EO (Deb and Wiklund, 2017).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%